Removal of fluoride from well water by modified iron oxides in a column system. Issue 5 (26th January 2016) - García-Sánchez, J.J.; Solache-Ríos, M.; Alarcón-Herrera, M.T.; Martínez-Miranda, V.
Abstract: The removal of fluoride from water by aluminum modified iron oxides (CP-Al) using a fixed-bed column adsorption system was investigated. Fixed-bed column experiments were carried out at different bed depths, and flow rate of 2 mL/min. The Bohart–Adams model and the Thomas model were applied to the experimental results. The adsorption efficiency decreases as the bed depth increases. The adsorption capacity for fluoride ions by CP-Al is higher for fluoride aqueous solutions than well water. The regeneration was accomplished by eluting a 0.1 M NaOH through the fluoride-loaded CP-Al bed. Scale-up and kinetic approach methods were used to calculate the design parameters from the breakthrough curves of fixed-bed column experiments. The parameters calculated from both methods indicated that they were suitable for fixed-bed column design.